The Translation Of Prepositions Between English And Arabic -sûrah Al-mûtaffȋfȋn A Comparative Study - Youmbai, Mohammed Yacine (University of Eloued جامعة الوادي, 2023)
Abstract: Translating between languages with distinct linguistic structures poses numerous challenges, and the translation of prepositions is no exception. This article explores the differences and the intricate task of translating prepositions between English and Arabic, two languages from different language families – Germanic and Semitic, respectively. Through an indepth analysis of the linguistic and cultural factors that influence preposition translation, this article sheds light on the complexities faced by translators. It examines the varying syntactic and semantic functions of prepositions, as well as the cultural nuances that affect their usage. By delving into these challenges, this article aims to provide a comparative study of the use of prepositions in the Quranic context between the Arabic and English languages as contribution to the field of translation studies.
Keywords: Arabic prepositions; cultural differences; English prepositions; semantic differences; Surat Al-Mutaffifin; translation; syntactic differences